The Experimental School in Bonneuil-sur-Marne…with Commentary from a North American Context - Vanier, Catherine; Malone, Kareen (Frontiers in Psychology, 2017)
This manuscript describes the operation of and principles that shape the activities of the children and role of psychoanalysis at the Experimental School in Bonneuil sur Marne. The ways in which the question of desire is "built into" the fabric and processes of the school are described in clear detail. Bonnueil's foundations in psychoanalysis, child analysis, and the anti-psychiatric movement of the 1960's and 1970's is also discussed. Particular attention is paid to the structure of the school as inside-outside in its organization. The commentary, from a North American psychologist's view attempts to further elaborate important principles and the pre-eminence of ethics and desire in the "life" at Bonneuil. The commentary also addresses views of psychoanalysis, especially Lacanian analysis, in North America in the context of how Bonneuil actually operates. Questions of how one can think psychoanalytically and institutionally (in the field of mental health) are taken up in both parts of the article.